Hidrodinamika dan Produk Sedimen terhadap Bendung Irigasi Keumala, Sungai Krueng Baro, Provinsi Aceh - Azmeri Azmeri; Hairul Basri; Devi Sundary; Yusni Eva Cus Endang; Faris Zahran Jemi (Jurnal Irigasi, 2020)
Keumala Dam is built on Krueng Baro River which is one of the strategic rivers in Aceh Province to irrigates the farmland and supplies drinking water for the community downstream. However, this river has a considerable issues due to its long path and passing through various geological formations, causing a high concentration of sediments in the river. Therefore, this study aimed to analyze the river hydrodynamics employing the HEC-RAS 5.0 software. The results of the study revealed that the flow capacity of sediment transport along the riverbed varies directly with the difference between the shear stress at the bottom sediment and the critical shear stress allowed for moving particles. Sediment transport occurred in all sediment samples from the upstream and downstream of Keumala Dam. The flow reduction due to the damming changed the channel and flow regime, while the decrease in water release reduced the floating and bottom sediment transport to the the downstream. The total sediment around the weir area at the normal discharge is 6,325,698.93 tons/year. Sedimentation around the weir is a severe problem as it can affect the function and performance of the weir and irrigation channel. Siltation due to sedimentation also closed the intake of Keumala PDAM. Thus, periodical dredging and transporting sediments from the bottom of the weir are necessary to overcome this problem. Dredging and transporting sediments will improve the Keumala weir performance to irrigates the Krueng Baro Irrigation Area. Thus, the discharge capacity of othe weir intake can be maintained to irrigate the farmland following the planned area.